2005
DOI: 10.1186/1476-072x-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Lumping or splitting: seeking the preferred areal unit for health geography studies

Abstract: Background: Findings are compared on geographic variation of incident and late-stage cancers across Connecticut using different areal units for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Still, the lack of qualifying results from the point-based SaTScan in low-density RC regions, when all areal-based tests passed our qualification criteria, was unexpected. Gregorio et al (2005) found general agreement between a point version of SaTScan and one applied to censusbased areal units, which are much larger aggregation units than ours, and had a wider range of unit populations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Still, the lack of qualifying results from the point-based SaTScan in low-density RC regions, when all areal-based tests passed our qualification criteria, was unexpected. Gregorio et al (2005) found general agreement between a point version of SaTScan and one applied to censusbased areal units, which are much larger aggregation units than ours, and had a wider range of unit populations.…”
Section: Discussionsupporting
confidence: 73%
“…If the point-based test had not failed, Kern would have a Consensus Cluster and Far Northern would have a Potential Cluster. Spatial tests that are adjusted for population density are more powerful in urban than rural areas (Gregorio et al., 2005). Still, the lack of qualifying results from the point-based SaTScan in low-density RC regions, when all areal-based tests passed our qualification criteria, was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support that data spatially aggregated to the tract level lead to results that contribute to increased capacity to identify local clusters [60]. We also show that data stability and greater consistency in the significant spatial patterns can be obtained through a temporal windowing approach, which is an important achievement for strategic planning when rates are based on small numbers.…”
Section: Discussionsupporting
confidence: 76%
“…All three choropleth maps in Fig. 2 display different spatial patterns, which illustrates the modifiable areal unit problem (MAUP) whereby the interpretation of a geographical phenomenon within a map depends on the scale and partitioning of the areal units that are imposed on the map (Waller and Got way, 2004; Gregorio et al ., 2005; Meliker et al ., 2009). In particular, zones with higher rate of late-stage diagnosis seem to shift east as the size of geographical units decreases.…”
Section: Resultsmentioning
confidence: 99%